On the wondrous stability of ALP dark matter - Alonso Álvarez, Gonzalo; Gupta, Rick S.; Jaeckel, Joerg; Spannowsky, Michael (Journal of cosmology and astroparticle physics, 2020)
The very low mass and small coupling of axion-like particles (ALPs) is usually taken as a guarantor of their cosmological longevity, making them excellent dark matter candidates. That said, Bose enhancement could stimulate decays and challenge this paradigm. Here, we analyze and review the cosmological decay of ALPs into photons, taking Bose enhancement into account, thereby going beyond the usual naive perturbative estimate. At first glance, this calculation seems to yield an exponentially growing resonance and therefore an extremely fast decay rate. However, the redshifting of the decay products due to the expansion of the Universe as well as the effective plasma mass of the photon can prevent an efficient resonance. While this result agrees with existing analyses of the QCD axion, for more general ALPs that can feature an enhanced photon coupling, stability is only ensured by a combination of the expansion and the plasma effects.
Gesehen am 26.05.2020